Group VIA phospholipase A2 deficiency in mice chronically fed with high-fat-diet attenuates hepatic steatosis by correcting a defect of phospholipid remodeling - Otto, Ann-Christin; Gan-Schreier, Hongying; Zhu, Xingya; Tuma-Kellner, Sabine; Staffer, Simone; Ganzha, Alexandra; Liebisch, Gerhard; Chamulitrat, Walee (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2019)
A defect of hepatic remodeling of phospholipids (PL) is seen in non-alcoholic fatty liver disease and steatohepatitis (NASH) indicating pivotal role of PL metabolism in this disease. The deletion of group VIA calcium-independent phospholipase A2 (iPla2β) protects ob/ob mice from hepatic steatosis (BBAlip 1861, 2016, 440-461), however its role in high-fat diet (HFD)-induced NASH is still elusive. Here, wild-type and iPla2β-null mice were subjected to chronic feeding with HFD for 6 months. We showed that protection was observed in iPla2β-null mice with an attenuation of diet-induced body and liver-weight gains, liver enzymes, serum free fatty acids as well as hepatic TG and steatosis scores. iPla2β deficiency under HFD attenuated the levels of 1-stearoyl lysophosphatidylcholine (LPC), lysophosphatidylethanolamine (LPE), and lysophosphatidylinositol (LPI) as well as elevation of hepatic arachidonate, arachidonate-containing cholesterol esters and prostaglandin E2. More importantly, this deficiency rescued a defect in PL remodeling and attenuated the ratio of saturated and unsaturated PL. The protection by iPla2β deficiency was not observed during short-term HFD feeding of 3 or 5 weeks which showed no PL remodeling defect. In addition to PC/PE, this deficiency reversed the suppression of PC/PI and PE/PI among monounsaturated PL. However, this deficiency did not modulate hepatic PL contents and PL ratios in ER fractions, ER stress, fibrosis, and inflammation markers. Hence, iPla2β inactivation protected mice against hepatic steatosis and obesity during chronic dietary NASH by correcting PL remodeling defect and PI composition relative to PC and PE.
Gesehen am 20.08.2019